Diversity and density of marine intertidal gastropods in tropical seagrass beds at Oransbari Bay, South Manokwari - West Papua - Duaitd Kolibongso; Frida A. Loinenak; Agnestesya Manuputty (Depik, 2023)
Gastropod communities are one of the important components of the food chain in seagrass meadows. This study aims to investigate the diversity of gastropods in the distribution of the seagrass beds at Oransbari Bay. This study was carried out in November 2022, using the line transect method. Data collection is carried out at three stations, where each station is divided into three transects. A total of 36 species consisting of 16 families and 5 orders, were recorded in this study. The total density of gastropods found in the waters of Oransbari Bay ranged from 5.77-9.43 ind/m2, with an average of 6.99 2.10 ind/m2. Conus sp. has the highest density value of any gastropod. Meanwhile, for seagrasses, five species from four clans and two families were obtained. The percent cover of seagrass ranges from 17.05 3.30% 58.90 22.90% with an average of 40.18 21.3%.Halophila minor and Thallasia hempricii showed a positive correlation with gastropod density. The value of the gastropod diversity index is in the medium category, the gastropod evenness index is in the stable category, and the gastropod dominance index is in the low category. The results of this study provide a base for a proper gastropod checklist at Oransbari Bay. Future research is recommended that involves a more detailed studies on the feeding ecology and habitat preference of the gastropods.Keywords:DiversityDistributionGastropodsSeagrass bedsOransbari bay